Deindustrialisation in Twentieth-Century Europe
XXVI, 490 p. 64 illus., 38 illus. in color.
Keywords: Exploring two large economies which were heavily affected by deindustrialisation in the late twentieth century, this book provides insights into the social movements that brought about and also challenged industrial reduction in Europe. Both the Ruhr region in Germany and the Northwest of Italy experienced major structural transformation from the 1960s as a result of deindustrialisation. With contributions from experts in the field, this collection provides a comparative overview of each region, examining policy implementation, class relations, the changing political economy and environmental impact. Analysing industrial and post-industrial landscapes, urban developments and labour relations, the authors place their transnational findings within the context of the wider literature on deindustrialisation in the global North. A much-needed contribution to deindustrialisation studies, which have traditionally focused on North America and the UK, this book is a useful read for those researching deindustrialisation and the social history of Europe. Stefan Berger is Professor of Social History and Director of the Institute for Social Movements at Ruhr University Bochum, Germany. He is executive chair at the Foundation History of the Ruhr and an Honorary Professor at Cardiff University in the UK. He co-edits, with Holger Nehring, Palgrave Studies in the History of Social Movements, and has published widely on comparative labour history, deindustrialisation studies, industrial heritage, historiography and nationalism. Stefano Musso is Associate Professor in the Department of Historical Studies at the University of Turin, Italy. He was general manager of the Institute for the Memory and Culture of Labour, Business, and Social Rights in Turin and President of the Italian Society for the History of Labour. He is a member of the editorial board of several Italian historical journals. Among his many publications on labour and business history is Storia del Lavoro in Italia (2015). Christian Wicke is Assistant Professor in Political History at Utrecht University, the Netherlands. He has worked in nationalism studies, deindustrialisation studies, and social movement studies and is particularly interested in the politics of history, memory and heritage, currently focussing on urban movements in the 1970s. With Stefan Berger and Sean Scalmer he recently edited Remembering Social Movements: Activism and Memory (2021).